The Use of Google Classroom in the Maharah Qiroah Learning in the Time of Covid 19 Eight Grades at Islamic High School : Penerapan Google Classroom dalam Pembelajaran Maharah Qiroah dimasa Covid 19 Siwa Kelas 8 di Sekolah Menengah Pertama Islam - Sholikhah, Mar'atus; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2023)
Researches are doing the google classroom application study of the maharah qiroah at the covi 19 of 8th grades at the SMPIT Darul Fikri Sidoarjo. The covid 19 made department decide that the study has been online since March 2020 to break the chain of infection. One is the application and one of the best platforms on e-learning is google classroom. The type of research used by researches is qualitative research. Data collection techniques used by researches are observation, interview, and documentation. While in data analysis techniquesuse interactive analysis techniques, researchers use three part interactive abalysis tehcniques of data reduction, data presentation, and conculasions. The result of this study :1)Maharah Qiroah learning using google classroom during covid 19 can help student were encourge to studying maharah qiroah, 2)Some contributing in the application of google classroom in the maharah qiroah learing during covid 19 are given more interesting materials and the flexibility of time to do the job, 3)Some of the inhibiting factors are the lack of steady internet connections as well as the inadequate student media.